STRENGTH AND FATIGUE ANALYSIS OF AN ENGINE PISTON - LIAO JunXiong; CHEN ZhenLei; LI JianCheng; LU XiangLin (Jixie qiangdu)
A finite element model including piston,connecting rod,cylinder liner etc.,has been established,which simulates the piston loading characteristics during its working process to the greatest extent. A coupled thermo mechanical analysis of the piston was presented in the paper. It creates an analytical and numerical model of the oil film and the contact pressure in the contact surfaces between piston and piston pin,piston pin and bush,piston skirt and cylinder liner. Moreover dynamic load and acceleration of the piston and con-rod are calculated at different crank angle using corresponding full engine dynamic model with a commercial software. Engineering application shows that the above analytical model is feasible and reliable,and the results agree with that of the corresponding experiment. The established analytical model can accurately reflect the real stress status of the piston pretty well during its working process. It is able to assess and evaluate the piston skirt pressure,stress and fatigue life of the concerned areas quantitatively. As a conclusion, it provides basic data for the optimization design of engine piston.